Is There a Relationship between Serum Anti-Mullerian Hormone Levels and Abortion Rates in Patients Who Received In vitro Fertilisation-Embryo Transfer Cycles? - Pinar Karacin; Serdar Dilbaz; Oya Aldemir; Berna Dilbaz; Yaprak Engin Ustun (Journal of Human Reproductive Sciences)
Background: The studies which investigated the relationship between anti-Mullerian hormone (AMH) level and abortion rate have conflicting results. Aims: This retrospective study aimed to evaluate the relationship between AMH levels and abortion in women who achieved pregnancy with in vitro fertilisation (IVF) treatment. Settings and Design: This retrospective study was conducted in the Department of Gynecology and Obstetrics, Etlik Zubeyde Hanim Women's Health Training and Research Hospital, between January 2014 and January 2020. Materials and Methods: Patients below 40 years of age who conceived after IVF-embryo transfer treatment during a 6-year period and had a serum AMH level measurement were included. The patients were divided into three groups according to the serum AMH levels as low AMH (L-AMH, ≤1.6 ng/mL), intermediate AMH (I-AMH, 1.61–5.6 ng/mL) and high AMH (H-AMH, >5.6 ng/mL). The groups were compared in terms of obstetric, treatment cycle characteristics and abortion rates. Statistical Analysis Used: The Mann–Whitney U-test was used in comparison of non-parametric data of two groups; the Kruskal–Wallis test was used to compare the data of more than two groups. When a statistically significant difference was found in the Kruskal–Wallis test result, the groups were compared in pairs using the Mann–Whitney U-test, and the groups that made a statistical difference were determined. The Pearson's Chi-square and Fisher's exact tests were used to compare the independent categorical variables. Results: L-AMH (n = 164), I-AMH (n = 153) and H-AMH (n = 59) groups were similar in terms of obstetric histories and number of cycles applied, with an abortion rate of 23.8%, 19.6% and 16.9%, respectively (P = 0.466). The same analyses were repeated in two subgroups under 34 years of age and above, and no difference was found in terms of miscarriage rates. The number of oocytes retrieved and the number of mature oocytes were higher in H-AMH group compared to intermediate and low groups. Conclusion: No relationship was found between serum AMH level and abortion rate in women who achieved clinical pregnancy with IVF treatment.